2002
DOI: 10.1007/s00259-002-0821-6
|View full text |Cite
|
Sign up to set email alerts
|

O-(2-[18F]Fluoroethyl)-L-tyrosine (FET): a tracer for differentiation of tumour from inflammation in murine lymph nodes

Abstract: High uptake of [(18)F]fluoro-2-deoxy- D-glucose (FDG) by inflammatory cells is a frequent cause of false positive results in lymph node (LN) staging by positron emission tomography. Previous studies suggest that radiolabelled amino acids may be more specific markers for viable tumour tissue than FDG. The aim of this study was to investigate quantitatively the uptake of FDG, [(3)H]methyl- L-methionine (MET) and O-2-([(18)F]fluoroethyl)- L-tyrosine (FET) in tumour-infiltrated and immunologically stimulated LNs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(67 citation statements)
references
References 25 publications
0
60
0
7
Order By: Relevance
“…However, recent rodent and clinical studies of L-11 C-MET-PET have demonstrated a definite increase in the tissue accumulation of L-11 C-MET in various inflammatory processes (28)(29)(30). The uptake of 18 F-FDG, L-11 C-MET, and L-18 F-FET, an amino acid transport ligand, in tumorinfiltrated and immunologically stimulated lymph nodes revealed increased uptake of 18 F-FDG and L-11 C-MET in both tissues (31). In contrast, L-18 F-FET proved to be a specific PET ligand for discrimination between tumorinfiltrated and inflammatory lymph nodes in the murine models studied.…”
Section: Discussionmentioning
confidence: 82%
“…However, recent rodent and clinical studies of L-11 C-MET-PET have demonstrated a definite increase in the tissue accumulation of L-11 C-MET in various inflammatory processes (28)(29)(30). The uptake of 18 F-FDG, L-11 C-MET, and L-18 F-FET, an amino acid transport ligand, in tumorinfiltrated and immunologically stimulated lymph nodes revealed increased uptake of 18 F-FDG and L-11 C-MET in both tissues (31). In contrast, L-18 F-FET proved to be a specific PET ligand for discrimination between tumorinfiltrated and inflammatory lymph nodes in the murine models studied.…”
Section: Discussionmentioning
confidence: 82%
“…18 F-DOPA demonstrated superior contrast ratios for lesions outside the striatum (23). The authors argued that 18 F-DOPA uptake occurs via both the LAT1 and the LAT2 systems, whereas 18 F-FET is mainly transported by LAT2 (29,32). However, the in vivo relevance of this phenomenon for the pharmacokinetics of 18 F-DOPA versus those of 18 F-FET remains unknown (33).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of such a hypothesis remains unclear, however. Animal studies have shown low or no uptake of 18 F-FET in inflammatory lesions (30), but false-positive results have been reported in human lesions such as abscesses (31). Little is known about the specificity of 18 F-TYR, but there were no false positive results in a series of 23 patients with non-small cell lung cancer or lymphoma (32).…”
Section: Discussionmentioning
confidence: 99%